9/y = -6
9 = -6y
y = 9/-6
y = -3/2 or -1.5
<>
2007-03-09 16:16:40
·
answer #1
·
answered by aeiou 7
·
0⤊
0⤋
9/y= - 6
y= 9/ -6 = -9/6 = - 1 3/6 = - 1 1/2 this mixed number is the simplest and most accurate answer possible in that form. It's decimal equivlent -1.5 is likewise the most accurate and simplest answer in that form. Either form may be the more convenient depending how it will be used next. Actually -9/6 may be the most convenient , also depending on the next use, but it is not the simplest form.
2007-03-09 16:36:27
·
answer #2
·
answered by Bomba 7
·
0⤊
0⤋
so it looks like this:-
9/y = -6
cross multiply y with -6
not you'll get 9 = -6y
not make multiplication division by taking -6 to the other side as the denominator
9/-6 = y
3 is common in 9 and -6 so divide both of them by 3
so you'll get -3/2 = y
or -1.5 = y
2007-03-09 16:19:05
·
answer #3
·
answered by Ashwin S 1
·
0⤊
0⤋
- 6 = 9 / y
- 6 y = 9
y = - 9 / 6 = - 3 / 2
2007-03-09 22:52:04
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
9/y = -6
9 = -6y {multiply both sides by y}
-3/2 = y {divide by -6}
2007-03-09 16:19:20
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
9/y = -6
multiply by y
9 = -6y
divide by 6
9/-6 = y
simplify
3/-2 = y
2007-03-09 16:22:40
·
answer #6
·
answered by Erin 2
·
0⤊
0⤋
-3/2
2007-03-09 16:15:32
·
answer #7
·
answered by Tartaglia 1
·
0⤊
0⤋
9/y = -6
Multiply both sides by y
9y/y = -6y
-6y = 9
Divide both sides by -6 to isolate y
-6y/-6 = 9/-6
y = 3/-2
y = -(3/2)
2007-03-09 16:31:43
·
answer #8
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
multiply both sides of equation by y.
9 y/y = -6y
reverse equation, and drop y/y.
-6y = 9
divide both sides by -6
y = -9/6
y = - 3/2
2007-03-09 16:17:46
·
answer #9
·
answered by Skeptic 7
·
0⤊
0⤋
cross multiply
9/y=-6/1
-6y=9
-6y/-6=9/-6
y=-9/6=-3/2
2007-03-09 21:28:13
·
answer #10
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋